Effect of date palm (Phoenix dactylifera L.) spikelets extract on the physicochemical and microbial properties of set-type yogurt during cold storage. (August 2021) - Almusallam, Ibrahim A.; Mohamed Ahmed, Isam A.; Babiker, Elfadil E.; Al-Juhaimi, Fahad Y.; Saleh, Ali; Qasem, Akram A.; Al Maiman, Salah; Osman, Magdi A.; Ghafoor, Kashif; Hajji, Hajji A.; Al-Shawaker, Adnan S.
Abstract: The aim of this study was to investigate the impact of different concentrations (0.5% and 1.0%) of date palm spikelet extracts (DPSEs) from Reziz (Rz) and Khalas (Kl) cultivars on the physicochemical and microbiological properties of cow's yogurt during cold storage. At the beginning of storage, DPSEs increased the water holding capacity (WHC), cohesiveness, springiness, adhesiveness, and a* values and decreased the viscosity, hardness, L*, and b* values of fortified yogurt compared to control. DPSEs did not affect the viable counts of LAB ( Streptococcus thermophilus and Lactobacillus bulgaricus ), pH, and acidity of yogurt at the beginning of storage; however, during storage, significant variations in these properties were observed between samples. As the storage time progressed, a significant reduction in pH, WHC, viable counts of LAB, viscosity, texture attributes, and color of the control yogurt was observed, whereas DPSE-fortified yogurts were stable or showed an increase in these properties, with some exceptions. Overall, DPSEs stabilized the gel matrix, maintained the growth of LAB, and improved the quality of yogurt during cold storage. In conclusion, DPSEs can improve the stability of yogurt gel during handling and storage because of the antioxidant activity of the extracts, thereby enhancing consumer's acceptability of the product. Highlights: Fortification of yogurt with date palm spikelets extracts (DPSEs) was investigated. DPSEs improved the water holding capacity and texture properties of yogurt. DPSEs maintained the growth of LAB in yogurt during cold storage. DPSEs improved physical and microbial properties of yogurt. DPSEs enhanced the overall quality of yogurt during cold storage.